Identification, Characteristics, and Fungicide Efficacy of Seed-Associated Fungi of Saposhnikovia divaricata in Northeast China - Zhang, Xue (Plant disease, 2024)
Saposhnikovia divaricata (Trucz.) Schischk. is one of the traditional medicinal herbs in Northeast China, and its roots are used for medicinal purposes. In 2020, a fungus isolated from S. divaricata seeds was observed to cause root rot of seedlings and leaf and stem spot of adult plants in Shuangyashan, Heilongjiang, China. Based on morphological and molecular data, isolates of all fungi were identified as Alternaria alternata. To our knowledge, this is the first report of A. alternata isolated from S. divaricata seeds in China. The carrying rate of S. divaricata seeds from 20 different collection sites reached 100% in 70% of the sites in Hulunbeier area, Inner Mongolia, China. The A. alternata isolate could infect the roots of cucumber, sorghum, mung bean, and maize seedlings and cause root rot. Considering the control of seed-associated fungal diseases, prochloraz 45% EW had the best control effect of 92.6%, followed by flusilazole 400 g liter-1 EC (88.9%) and azoxystrobin + propiconazole 18.7% SE (70.7%) of 15 fungicides. Further field control efficacy showed that 45% prochloraz EW had an 80% control efficacy on the disease at a dose of 0.225 g liter-1. It is recommended that soaking seeds and spraying are the best treatments for controlling seed-associated fungi and leaf spot on S. divaricata caused by A. alternata. Therefore, the aforementioned methods can effectively prevent the occurrence of fungal diseases of S. divaricata and provide a way to reduce reinfestation in the field